The normative claims of Brazil's democratic ethos: Bourdieu's habitus, critical theory, and social philosophy - Nythamar de Oliveira (Pontifícia Universidade Católica do Rio Grande do Sul, 2012)
This paper argues for an interdisciplinary interlocution between social theory and social philosophy in order to recast the problem of normativity in social practices, especially within Brazil's democratic ethos. By resorting to insights from critical theory and social epistemology, the essay proposes to reexamine Bourdieu's conception of habitus so as to contribute to a moderate social constructionism that cannot be reduced to a postmodernist discourse or to a variant of relativism.